Comprehensive first-principles study of transition-metal substitution in the γ phase of nickel-based superalloys. (June 2018) - Chen, Weiliang; Xing, Weiwei; Ma, Hui; Ding, Xueyong; Chen, Xing-Qiu; Li, Dianzhong; Li, Yiyi
Abstract: In order to elucidate the role of various M -alloying additions in the fcc-type γ phase of nickel-based superalloys, we have performed a comprehensive and systematical computation on all 3 d -, 4 d - and 5 d - M alloying additions substituting in the Ni lattice using the same standard of the first-principles calculations within the framework of the density functional theory. The results show that the substitution enthalpies of Sc, Ti, V, Mn, Fe, Co, Zn, Zr, Nb, Hf, Ta, and Pt are negative, while the others elements have positive substitution enthalpies. To further explore the contributions of various factors to the substitution enthalpy, we have attempted to divide the substitution enthalpy into two parts. The first one is the mechanical deformation energy caused by the atomic volume change because of the M -alloying additions substituting in fcc Ni and the other one is the chemical and magnetic energy through electronic hybridizations and local magnetic interactions. It is found that the substitution enthalpy is a consequence of the balancing of these two contributions. Furthermore, we have attempted to correlate their mechanical deformation energies with metallic atomic radii of substitutional M -alloying addition with respect to Ni, and the chemical and magnetic energies with transferred charges between M -alloying addition and Ni, which are indeed associated with the so-called electronegativity difference.